TRAINING OF FUTURE OFFICERS FOR PROFESSIONAL ACTIVITIES AS A PEDAGOGICAL PROBLEM - RUDYNSKY, Vitaly (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2023)
We analyze the professional training of future officers for professional activities at HMEI through the prism of their readiness to carry out activities that ensure Ukraine's national security and defence. Readiness is considered a subjective state of an individual with the ability and readiness to perform assigned military tasks according to the speciality, with his desire for effective performance. Practical training of future officers for professional activities is emphasized as one of the critical requirements for managers and teachers of higher education institutions, as it contributes to their quick adaptation to working conditions, further qualification improvement, and professional growth. The cadets' study of academic disciplines, with the predictable application of inter-subject connections, should contribute to their multidimensional competence development. Integrated, interdisciplinary and problem-based learning models are among the essential directions of implementing the educational process of cadets, which influence professional training and fully prepare them for the military profession and have become widespread in VVNIZ. Attention is focused on the systematic level of training of future officers for professional activity from low to high with a consistent transition of the prospective officer's readiness for disciplinary activity performance by officers of various functions, a significant one among which is the military-pedagogical one (the future officer is not only a military officer but also a teacher and organizer of education and training); a high degree of social responsibility, conservatism, strict regulation of the conditions of an officer's professional activity; the ability to effectively perform official duties and the adoption of the appropriate personal lifestyle, way of thinking, system and values by the cadets of VVNIZ. Consideration of the training of future officers for military professional activity proves the importance of two types of readiness for such activity - general and situational (according to situations). Situational - is close to establishing such training and its pre-start state, while available - preparation is competent, professional, and long-term. The analysis of the outlined problems of training future officers for professional activity proves that the identified research areas only affect specific training components.